Intertextuality - Allen, Graham 1963- (Routledge, Taylor & Francis Group, 2022)
"This successful introduction to intertextuality deftly introduces this crucial area and relates its significance to key theories and movements in the study of literature. The third edition is updated to includes a brand new chapter, looking at intermediality, and how the study of intertextuality has changed over the last ten years. Offering a clear guide to this crucial area, Graham Allen outlines the history and contemporary use of the term incorporates a wealth of illuminating examples from literature and culture examines the politics and aesthetics of the term relates intertextuality to global cultures and new media Looking at intertextuality in relation to literary and critical theory as well as contemporary culture and media, this book offers a fascinating and useful approach to all aspects of literary studies, especially those dealing with adaptation, media, or comparative studies"--
Keywords: Intertextualität; Intertextuality